Зв’язок мехатроніки з іншими напрямками науки - Лучанінова, О. Ю. (ХНУРЕ, 2021)
The current standard of basic terms in the field of mechatronics has been analyzed. It was given to an understanding about "ravnevy pidhid" to mechatronics. This allows you to tie mechatronics, microsystem technology and nanoindustry between you. The power supply has been supplied about the expansion of the mechatronics technology from the computer management to the management of the facility.
Keywords: мехатроніка